A performance do narrador em Clarice Lispector e em Hilda Hilst: O narrar que (se) frustra - Reguera, Nilze Maria de Azeredo [UNESP] (My University, 2007)
This paper aims at analyzing at which extent the narrators in Antes da ponte Rio-Niterói by Clarice Lispector, and in Osmo by Hilda Hilst, undertake, in their own fashion, a dramatized narration by resorting to procedures such as fait divers; a seemingly didatic presentation of the facts; a reiterated concern with the text reception; irony and self-referentiality.

Busca-se analisar em que medida os narradores de “Antes da ponte Rio-Niterói”, de Clarice Lispector, e de “Osmo”, de Hilda Hilst, empreendem, cada qual a seu modo, um narrar dramatizado, dado por meio da utilização de recursos como: fait divers, uma aparente apresentação “didática” dos fatos, uma reiterada preocupação com a recepção dos textos, ironia, auto-referencialidade.
The performance of the narrator in Clarice Lispector and Hilda Hilst: The (self) frustrating narration
Keywords: Hilst; Lispector; Narrator; Performance